2021
DOI: 10.1007/s00586-021-07064-z
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a nomogram and web calculator for the risk of new vertebral compression fractures and cement leakage after percutaneous vertebroplasty in patients with osteoporotic vertebral compression fractures

Abstract: Purpose The aim of this work was to investigate the risk factors for cement leakage and new-onset OVCF after Percutaneous vertebroplasty (PVP) and to develop and validate a clinical prediction model (Nomogram). Methods Patients with Osteoporotic VCF (OVCF) treated with PVP at Liuzhou People’s Hospital from June 2016 to June 2018 were reviewed and met the inclusion criteria. Relevant data affecting bone cement leakage and new onset of OVCF were collected. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…There were several studies on the latter shown that patient's age, associated comorbidities, functional status, etc. could lead the patient not being discharged as planned (26,27). Furthermore, as more data being obtained, models can be retrained over time to improve prediction accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies on the latter shown that patient's age, associated comorbidities, functional status, etc. could lead the patient not being discharged as planned (26,27). Furthermore, as more data being obtained, models can be retrained over time to improve prediction accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that prolonged menopause and low bone mineral density (BMD) may increase the risk of re-fracture after PVP [ 16 ]. Body mass index (BMI), preoperative multisegmental vertebral compression fractures, and dispersion degree of bone cement have also been reported to be related to re-fractures after PVP or PKP [ 17 19 ]. Overall, the relationship between the occurrence of vertebral fractures and PVP/PKP surgery remains controversial due to the varying results of clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporotic vertebral compression fractures (OVCFs) have become a frequent low-energy injury with the accelerated aging of the population worldwide ( 1 , 2 ). Approximately 1.4 million patients worldwide are diagnosed with fresh OVCF each year ( 3 ). Patients suffer from chronic back pain, reduced mobility and daily activities, poor quality of life, and the accompanying heavy financial burden.…”
Section: Introductionmentioning
confidence: 99%